Analysis of the Diagnostic Consistency of Chinese Medicine Specialists in Cardiovascular Disease Cases and Syndrome Identification Based on the Relevant Feature for Each Label Learning Method - 许朝霞 徐璡 颜建军 王忆勤 郭睿 刘国萍 燕海霞 钱鹏 洪毓键 (Chinese journal of integrative medicine, 2015)
Objective：To analyze the diagnostic consistency of Chinese medicine（CM） specialists in patients with cardiovascular disease and to study syndrome classification and identification based on the multi-label learning method.Methods：Using self-developed CM clinical scales to collect cases,inquiry information,complexity,tongue manifestation and pulse manifestation were assessed.The number of cases collected was 2,218.Firstly,each case was differentiated by two CM specialists according to the same diagnostic criteria.The consistency of the diagnosis based on Cohen’s Kappa coefficient was analyzed.Secondly,take the same diagnosis syndromes of two specialists as the results of the cases.According to injury information in the CM scale ＂yes＂ or ＂no＂ was assigned ＂1＂ or ＂0＂,and according to the syndrome type in each case ＂yes＂ or ＂no＂ was assigned ＂1＂ or ＂0＂.CM information data on cardiovascular disease cases were established.We studied CM syndrome classification and identification based on the relevant feature for each label（REAL） leaming method,and the diagnostic rate of the syndrome was studied using the REAL method when the number of features selected was 5,10,15,20,30,50,70,and 100,respectively.Results：The syndromes with good diagnostic consistency were Heart（Xin）-qi deficiency,Heart-yang deficiency,Heart-yin deficiency,phlegm,stagnation of blood and stagnation of qi.Syndromes with poor diagnostic consistency were heartblood deficiency and blood deficiency of Heart and Liver（Gan）.The highest diagnostic rates using the REAL method were Heart-yang deficiency followed by Heart-qi deficiency.A different number of features,such as 5,10,15,20,30,40,50,70,and 100,respectively,were selected and the diagnostic accuracy based on five features showed the highest diagnostic accuracy.The top five features which had a strong correlation with the syndromes were in accordance with the CM theory.Conclnsions：CM syndrome differentiation is strongly subjective and it is difficult to obtain good diagnostic consistency.The REAL method fully considers the relationship between syndrome types and injury symptoms,and is suitable for the establishment of models for CM syndrome classification and identification.This method can probably provide the prerequisite for objectivity and standardization of CM differentiation.